Social buffering suppresses fear-associated activation of the lateral amygdala in male rats: behavioral and neurophysiological evidence - Fuzzo, Felipe; Matsumoto, Jumpei; Kiyokawa, Yasushi; Takeuchi, Yukari; Ono, Taketoshi; Nishijo, Hisao (Frontiers in Neuroscience, 2015)
In social mammals, the presence of an affiliative conspecific reduces stress responses, a phenomenon referred to as ‘social buffering’. In a previous study, we found that the presence of a conspecific animal ameliorated a variety of stress responses to an aversive conditioned stimulus (CS), including freezing and Fos expression in the lateral amygdala (LA) of male rats. Although these findings suggest that the presence of a conspecific animal suppresses neural activity in the LA, direct neurophysiological evidence of suppressed activity in the LA during social buffering is still lacking. In the present study, we analyzed freezing behavior and local field potentials in the LA of fear-conditioned rats in response to the CS, in the presence or absence of a conspecific. After auditory aversive conditioning, the CS was presented to the conditioned rats in the presence or absence of a conspecific animal, on two successive days. The presence of a conspecific animal significantly decreased the mean peak amplitudes of auditory evoked field potentials, gamma oscillations (25 – 75 Hz) and high frequency oscillations (100 – 300 Hz) in the LA. Furthermore, magnitudes of these neural responses positively correlated with freezing duration of the fear-conditioned rats. The results provide the first electrophysiological evidence that social buffering suppresses CS-induced activation in the LA, which consequently reduces conditioned fear responses.